The Non-Linear Impact of Share Repurchases on Liquidity: The Case of Listed Companies in Thailand - Thanatawee, Yordying (Asian Journal of Business and Accounting, 2016)
Manuscript type: Research paper Research aims: The purpose of this paper is to examine the impact of open market share repurchases on stock liquidity of listed companies in Thailand. Design/ Methodology/ Approach: The sample includes 3,055 actual share repurchases made by 75 listed firms in the Stock Exchange of Thailand (SET) over a period of 13 years from 2002 to 2014. Multiple regressions are used to examine linear and non-linear relationships between actual share repurchases and liquidity measures. Research findings: Results show that actual share repurchases generally have beneficial impacts on liquidity. This is indicated by narrower bid-ask spreads and smaller price impact as firms repurchase more shares. Nonetheless, the impact of share repurchases on stock liquidity of Thai listed firms tends to be nonlinear. At low level share repurchases, repurchasing more shares increases liquidity but at high level share repurchases, acquiring more shares impair liquidity. Theoretical contributions/ Originality: The findings of this paper shed some light on the long debate regarding the impact of share repurchases on liquidity by showing that the relationship between stock repurchases and liquidity is non-linear. It is found that share repurchases have a positive effect on stock liquidity if firms repurchase small number of shares per day (price support hypothesis). However, share repurchases may have a detrimental effect on stock liquidity if firms buy back shares aggressively (information asymmetry hypothesis). Practitioner/ Policy implications: The study has demonstrated that a share repurchase programme can be used as an effective tool to enhance stock liquidity if it is implemented properly. Research limitations/ Implications: Since the findings of this study may be applicable only to listed companies in Thailand, future research should try to extend the analysis to other emerging markets. Keywords: Liquidity, Share Repurchases, Thailand JEL Classification: G14, G32, G35